2020
DOI: 10.1088/1361-6528/ab9327
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanism for nanotips in high electric fields

Abstract: In this work we show using atomistic simulations that the biased diffusion in high electric field gradients creates a mechanism whereby nanotips may start growing from small surface asperities. It has long been known that atoms on a metallic surface have biased diffusion if electric fields are applied and that microscopic tips may be sharpened using fields, but the exact mechanisms have not been well understood. Our Kinetic Monte Carlo simulation model uses a recently developed theory for how the migration bar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Most of these breakdown events are related to the presence on the cathode of micro/nano-protrusions, whose shape and density depend on the surface roughness 4 . Besides, such protrusions may also emerge and evolve via electromigration 5 and field-induced surface atom diffusion 6 . Locally enhancing at their apex the high applied electric field, these protrusions act as field electron emitters.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these breakdown events are related to the presence on the cathode of micro/nano-protrusions, whose shape and density depend on the surface roughness 4 . Besides, such protrusions may also emerge and evolve via electromigration 5 and field-induced surface atom diffusion 6 . Locally enhancing at their apex the high applied electric field, these protrusions act as field electron emitters.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even at moderate electric field val-ues the formation of such surface protrusion becomes expectable. Moreover, once the protrusion growth is initiated, positive feedback loops, as reported in [39,40], can become active, finally leading to the breakdown events.…”
Section: Discussionmentioning
confidence: 99%
“…Recent kinetic Monte Karlo simulations [17] have shown that starting from surface protrusions of a few nm size, larger scale field-enhancing tips can grow due to the biased diffusion effect [18,19]. However, the dynamics and the possible mechanisms behind the formation of the initial nano-protrusions has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…[35,37,[45][46][47][48]). We use the same ν also for second-nearest jumps and exchange processes, as discussed in [49]. The migration energy E m will depend on the local environment of the transitions; i.e.…”
Section: Theorymentioning
confidence: 99%